Influence of Mn on dry yield and nutrient uptake by new jute variety BJRI Tossa-7 - Rahman, Mariha; Mohsin, Gazi Md; Sarker, Md Bayzid; Gani, Md Nasimul; Hossain, Mohammad Enayet (International Journal of Agricultural Research, Innovation and Technology, 2024)
A field experiment was conducted during the year 2018-2019 at the vital place of Bangladesh Jute Research Institute (BJRI), Dhaka. The aim of the study was to evaluate the influence of Mn fertilizer on the dry matter yield and potential nutrient uptake of the newly developed jute variety BJRI Tossa jute-7. The treatments used in the experiments were T1: Control, T2: RDF sole (N90P10 K30 S20kg/ha), T3: RDF + 1 kg Mn/ha, T4: RDF + 2 kg Mn/ha, T5: RDF + 3 kg Mn/ha and T6: RDF + 4 kg Mn/ha. Mn application had a favorable effect on the dry matter yield of jute. Among the fertilizers of Mn with RDF, interaction promoted the dry yield biomass compared to sole RDF and control. Maximum dry matter yield (leaves + shoots + roots) achieved (20000 kg/ha) with T5 (RDF + 3 kg Mn/ha) and minimum (6421 kg/ha) in T1 (control). Study indicated that it needs to apply Mn to obtain optimum yield production. The interaction effect of Mn, NPK and S fertilizer significantly influenced nutrient uptake by the jute plant. The uptake of nutrient found highest N (218.9 kg/ha) in T5, P (92.75 kg/ha) in T3, K (239.73 kg/ha) with T6, S (19.59 kg/ha) in T4, Fe (0.64 kg/ha) in T5, Zn (0.38 kg/ha) in T5 and Mn (0.63 kg/ha) recorded in T6. The amount of micro nutrient uptake may be arranged in the order of Mn >Zn> Fe. Considering the highest uptake of major element, it can be kept as in the order of K > N>P>S. Study indicated that a higher rate of nutrient uptake was promoted dry matter accumulation in jute. Research revealed that the rate of nutrient uptake maximized with the addition of Mn in the RDF treatment. Hence, it could be concluded that applying RDF + 3 kg Mn/ha may be a suitable dose for optimum yield production of jute. Yet, in order to draw a sound conclusion, repeating the experiment is needed. In the future, the study will be a guideline for further investigation. Int. J. Agril. Res. Innov. Tech. 14(1): 87-95, June 2024